2020
DOI: 10.1111/ocr.12448
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus brevisCD2 attenuates traumatic oral lesions induced by fixed orthodontic appliance: A randomized phase 2 trial

Abstract: Objective: To evaluate the effect of the probiotic Lactobacillus brevis CD2 on the prevention of early traumatic oral lesions induced by a fixed orthodontic appliance. Settings and Sample Population:Twenty orthodontic patients (14-57 yo) were recruited from a private clinic. Subjects and Methods:In a phase 2, double-blind clinical trial, all patients were randomly allocated (1:1 ratio) to a 21-day course of soluble tablets containing L brevis CD2 (4 billion colony-forming units after breakfast, lunch and dinne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…Silva et al 13 showed that L. brevis CD2 soluble tablets used in the first 21 days of orthodontic treatment reduced the length of traumatic oral lesions from 4.9 to 2.5 days. Oral pain related to traumatic lesions was also alleviated with the use of probiotics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Silva et al 13 showed that L. brevis CD2 soluble tablets used in the first 21 days of orthodontic treatment reduced the length of traumatic oral lesions from 4.9 to 2.5 days. Oral pain related to traumatic lesions was also alleviated with the use of probiotics.…”
Section: Discussionmentioning
confidence: 99%
“…A study reported that Lactobacillus brevis reduced almost 50% of the persistence of traumatic oral lesions in patients with fixed orthodontics. 13 Considering the significant effect of the pain and ulcers of orthodontic treatments on patients’ quality of life and the lack of definite treatment or prevention method, this study compared the effect of probiotic lozenges along with orthodontic wax on the amount of pain and ulcers in patients undergoing fixed orthodontic treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Examples are included that focus on pain associated with gastrointestinal issues (ulcerative colitis and irritable bowel), osteoarthritis, probiotics and headaches, post-surgical pain, neurologic and visceral pain, menopausal status, the risk-benefit role of opioids, the connections between microbiota and microglia activation, and gut microbiota as pertains to pain hypersensitivity vs. tolerance. While a variety of microbiome studies are described within the review articles in Table 1, the most recent preclinical and clinical trials from the past 2-3 years are highlighted in Table 2 [52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71]. Several areas of activity are notable.…”
Section: Painmentioning
confidence: 99%